SOME REFINEMENTS OF THE HEINZ INEQUALITIES - Xue, Jianming (Italian Journal of Pure and Applied Mathematics, 2015)
This paper aims to discuss Heinz inequalities for unitarily invariant norms. We present some refinements of the Heinz inequalities for matrices due to Kittaneh [Integr. Equ. Oper. Theory, 68:519-527, 2010]. Our results generalize the results shown by Feng [J. Inequal. Appl., 2012:18, 2012], Wang [J. Inequal. Appl., 2013:424, 2013] and Yan et al. [J. Inequal. Appl. 2014:50, 2014].